Analysis of the Influence of Population, Human Development Index, Gross Regional Domestic Product and Social Expenditures on Poverty in Kotamobagu City - Garus, Firdaus Marselino; Engka, Daisy S. M.; Masloman, Irawaty (Formosa Journal of Applied Sciences, 2024)
The aim of this research is to determine the relationship between the population of Kotamobagu City, gross regional output, human development index and community welfare on the degree of poverty in question. This research uses second order data, namely time series from Kotamobagu City and the Central Statistics Agency of North Sulawesi Province. Data collection was carried out using multiple line regression analysis techniques using Eviews 12 software. The conclusion of a study shows that the population size of the poverty rate is small but has a positive impact on Kotamobagu City. There is a negative correlation between the poverty level of Kotamobagu City and the human development index. Kotamobagu City's gross regional product has an important and detrimental impact on the amount of poverty in the city. Social spending in Kotamobagu City influences poverty levels both positively and negatively.